Primera edición - investigación educativa y sociedad: avances, apuestas y realidades en Colombia (2021)
Eng:This article is presented within the framework of the research assigned to the Interinstitutional Doctorate in Education of the Universidad del Valle, on the historical phenomenon of displacement in Colombia, emphasizing the use of narratives as a pedagogical resource for the reconstruction of historical memory, The power of narrative biography as a research method is explored, and it is committed to promoting the breaking of the silences imposed by the system, a work that must be exercised from the School through the reconstruction of individual and collective memory from the narratives of the anonymous subject in a condition of forced displacement. It begins by outlining the controversial situation and its relevance in the school context, then the proposal of how to investigate, its justification, and finally the investigative committee of the author is presented.